PENGEMBANGAN MEDIA SMART BOX INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR MURID MAPEL PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR - Tifany Rizqika Annisa’; Kurniana Bektiningsih (JS (JURNAL SEKOLAH), 2026)
Abstact: This study aimed to develop an Interactive Smart Box learning media to improve fourth-grade elementary students’ learning outcomes in Pancasila Education. The research employed a Research and Development method using the ADDIE model. Instruments included expert validation questionnaires, teacher and student response questionnaires, and pretest–posttest assessments. Data were analyzed using percentage analysis, paired sample t-test, and N-gain analysis. Results indicated that the media was highly feasible (media 90%; material 97%), highly practical (teacher 92%; students 95%), and moderately effective in improving learning outcomes, as shown by a medium N-gain score. Keyword: Interactive Smart Box, Pancasila Education, learning Outcomes   Abstrak: Penelitian ini bertujuan mengembangkan media Smart Box Interaktif untuk meningkatkan hasil belajar murid pada mata pelajaran Pendidikan Pancasila kelas IV sekolah dasar. Penelitian menggunakan metode Research and Development dengan model ADDIE. Instrumen penelitian meliputi angket validasi ahli, angket respons guru dan murid, serta tes pretest dan posttest. Data dianalisis menggunakan analisis persentase, uji paired sample t-test, dan uji N-gain. Hasil penelitian menunjukkan media sangat layak (media 90%; materi 97%), sangat praktis (guru 92%; murid 95%), serta cukup efektif meningkatkan hasil belajar dengan nilai N-gain kategori sedang. Kata Kunci: Smart Box Interaktif, Pendidikan Pancasila, Hasil Belajar